Women's views on contact with a health visitor during pregnancy: an interview study. (2019) - Olander, Ellinor K.; Aquino, Maria Raisa Jessica (Ryc); Chhoa, Celine; Harris, Erica; Lee, Suzanne; Bryar, Ros
Abstract: Aim: To explore recent mothers' views of the health visiting antenatal contact in England. Background: English health visitors are mandated to be in contact with all women in the third trimester of pregnancy. The aim of this antenatal contact is to assess the needs of the family before the birth and support preparation for parenthood. Recent data show that this contact is provided fragmentarily and not always face-to-face. More information on how women view this contact could inform service provision. Methods: Twenty-nine mothers with a baby less than 1 year old were recruited via social media and word of mouth. Having had antenatal contact with a health visitor was not a requirement to participate in the study. Women took part in face-to-face or phone interviews and all recordings were transcribed verbatim. Data were analysed using systematic thematic analysis. Findings: Eleven women had contact with a health visitor during pregnancy: nine through a home visit, one via a letter and one via a phone call. The remaining 18 women were asked about what they would have wanted from an antenatal contact. Three themes were identified: relationship building, information provision, and mode and time of contact. Some participants who had experienced a home visit reported building rapport with their health visitor before the postnatal period, but not everyone had this experience. Women reported requesting and receiving information about the health visiting service and the role of the health visitor. Finally, women suggested different modes of contact, suggesting a letter or that the information about health visiting could be provided by a midwife. A few women preferred a home visit. These study findings show women were unclear regarding the aim of the health visitor antenatal contact. As such, the contact is unlikely to reach its full potential in supporting parents-to-be.